Effects on Service Improvement of Transport in view of urban sustainability - Seiichi Kagaya; Masaru Uraoka; Ami Kato (European Regional Science Association (ERSA), 2011)
In these years, the urban planning system has been reconsidered in terms of sustainable policies. The sustainability in urban areas involves attempts of urban development including environmental, social and economic improvements, policies and practices in the next generation stage. In most of Japanese cities and towns, transport planning was based on the efficiency of car vehicles use until now. As a result, traffic congestion occurred and caused slower speeds, longer times of car vehicles in a downtown area, while car drivers used the car vehicles even for walking distance. Therefore, it is necessary for the cities to improve the transport service in their areas including walking, cycling, and public transit oriented system and so on. These modes contribute to the urban sustainability positively and correspond to the appropriate mobility of the people. In this study, first of all, the effect on the introduction of a new public transport system, namely, an extension of tram car system was examined. Here, the impacts on surrounding areas due to tram line extension are assessed in view of the sustainable urban planning. In the next objective, the effects on the improvement of an underground passage, which is more convenient for pedestrian to go around the downtown area, were evaluated. The practical research and study was examined in Sapporo City, Japan. The results of analysis show in the following aspects: 1) the inhabitants expects the extension of tramcar in the supposed area, 2) people also expect activeness and attractiveness resulted from the extension of tram car line, 3) the pedestrians expect to be capable more choice of shop facilities, particularly, in rainy or snowy weather due to the use of underground passage, 4) the underground passage stimulates the behaviors of visitors between two commercial areas which exist separately to stay and enjoy for longer time.
Keywords: 330